ADVANCED STUDENTS’ SPEAKING ANXIETY AND THEIR STRATEGIES TO REDUCE ANXIETY DURING ONLINE LEARNING - Yuliana Ayu Pertiwi; Ika Hidayanti (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Anxiety becomes one of obstacles which is probably experienced by advanced-level students when they are speaking class. Nevertheless, the students should deal with this situation. This study examined the students’ anxiety level and their solutions in online speaking classes. Descriptive quantitative and qualitative were used in this study. In collecting the data, a questionnaire consisting fifteen statements and interview with five questions were employed. The subject was 33 English-speaking learners in the fourth English semester at the Department of English Education, University of Islam Malang. They were required to fill out a questionnaire about speaking anxiety through Google Form. To analyze the data, descriptive analysis was used. The results obtained from this study were; the fourth-semester students tended to feel confident during online learning without feeling significant anxiety; the students revealed their solutions to cope with their anxiety such as by applying memory, metacognitive, social, affective, compensation, and cognitive strategies so that they could feel confident practicing speaking during online learning. Furthermore, the most strategies utilized was the affective strategy. This strategy focused on the way the students learnt to speak and become more confident. It can be concluded that students could feel confident, and they needed to apply one of the speaking strategies to reduce speaking anxiety.